Metal modified molecular sieve and preparation method thereof

By ion exchange and high-temperature hydrothermal roasting with various metal element salt solutions, the problem of small adsorption of FAU molecular sieve adsorbents in one way is solved, and the adsorption amount and thermal stability are improved, which is suitable for industrial-grade high efficiency Adsorption application.

CN119118149APending Publication Date: 2024-12-13CHINA ENERGY GRP NINGXIA COAL IND CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411265794.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The single-pass adsorption amount of existing FAU molecular sieve adsorbents is small and requires frequent regeneration, resulting in large energy consumption and unfavorable industrial production.

Method used

By ion exchange of FAU molecular sieve with a salt solution containing metal elements such as Fe, K, Cu, Mn or Zn, a composite FAU molecular sieve is formed, and calcined under high temperature hydrothermal conditions to fix a variety of metal elements in the molecular sieve pores. Improve adsorption amount and thermal stability.

Benefits of technology

It significantly improves the single-pass adsorption amount and adsorption efficiency of molecular sieves, reduces the adsorption calorific value, and forms a stable and highly selective adsorbent, suitable for high-temperature industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119118149A_ABST
    Figure CN119118149A_ABST
Patent Text Reader

Abstract

The invention provides a metal modified molecular sieve and a preparation method thereof. The preparation method comprises the following steps: I) mixing an FAU molecular sieve with a metal salt solution and carrying out ion exchange to obtain a composite FAU molecular sieve, the metal salt solution being a salt solution of two or more metals selected from Fe, K, Cu, Mn or Zn; and II) carrying out first roasting on the composite FAU molecular sieve to obtain the metal modified molecular sieve. The problem that the FAU molecular sieve adsorbent in the prior art is small in one-way adsorption capacity can be solved, and the method is suitable for the field of molecular sieve adsorbents.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of molecular sieve adsorbents, and in particular to a metal-modified molecular sieve and a preparation method thereof. Background Art

[0002] FAU molecular sieve is a kind of aluminosilicate, which has the characteristics of uniform pore size, regular crystal structure, rich pore system, large specific surface area, and good thermal stability. It is considered to be the preferred adsorbent material for removing oxygenated compounds from olefins. FAU type (X, Y type) molecular sieve, pore size is about 0.74nm. When used for olefin purification, FAU molecular sieve has high adsorption heat, usually requires pre-load, and will adsorb some olefins during the adsorption purification process. Therefore, the research and development of FAU molecular sieve adsorbents focuses on three aspects: first, selective adsorption of oxygenated compounds, as little adsorption of olefins as possible; second, effectively reducing adsorption heat; third, effectively increasing the adsorption capacity of the adsorbent, adsorption purification depth, etc. The use of adsorption method to separate substances has been widely used in petroleum cracking and refinery catalytic cracking. At present, the research on adsorption separation process is mainly used for the adsorption method to remove oxygenated compounds from C4 and above hydrocarbons.

[0003] In order to meet production needs, the purity requirements of C4 and above raw materials are constantly increasing. Among them, the removal of impurities such as H2O, methanol, dimethyl ether and other oxygen-containing compounds is an extremely important process. In the past, solid adsorbents were mainly based on porous inorganic materials, such as silica sol and molecular sieves. The adsorption capacity of these materials is mainly determined by their specific surface area and the affinity of the surface to the adsorbed molecules. However, due to the limited specific surface area of ​​these adsorbent materials (usually no more than 500m 2 / g), so the adsorption capacity is also limited. Compared with other adsorbents, FAU molecular sieve adsorbent has stronger polarity, abundant micropores and better stability, and is widely used in the adsorption and purification process of various gases and liquids.

[0004] However, the FAU molecular sieve adsorbent in the prior art has limited single-pass adsorption capacity and requires frequent regeneration, so in actual industrial production, it will result in disadvantages such as high energy consumption and the need for frequent activation. Summary of the invention

[0005] The main purpose of the present invention is to provide a metal-modified molecular sieve adsorbent and a preparation method thereof, so as to solve the problem of small single-pass adsorption capacity of FAU molecular sieve adsorbent in the prior art.

[0006] In order to achieve the above-mentioned object, according to the first aspect of the present invention, a method for preparing a metal-modified molecular sieve is provided, the preparation method comprising: I) mixing a FAU molecular sieve with a metal salt solution and performing ion exchange to obtain a composite FAU molecular sieve, wherein the metal salt solution is a salt solution containing two or more metal elements selected from Fe, K, Cu, Mn or Zn; II) performing a first calcination on the composite FAU molecular sieve to obtain a metal-modified molecular sieve.

[0007] Furthermore, the temperature of the first calcination is 400-650° C.; preferably, the time of the first calcination is 1-6 hours.

[0008] Furthermore, the method for preparing the metal salt solution comprises: mixing a first oxide with a first acid solution to obtain a metal salt solution; preferably, the first oxide comprises a waste catalyst; preferably, the method for preparing the metal salt solution comprises: removing impurities and calcining the waste catalyst, and then mixing it with the first acid solution to obtain a metal salt solution; preferably, the solid-liquid ratio of the first oxide to the first acid solution is 1:50-60 g / mL; preferably, the waste catalyst comprises one or more of a waste Fischer-Tropsch catalyst, a waste supported metal catalyst or a waste supported metal adsorbent; more preferably, the waste Fischer-Tropsch catalyst comprises one or more of an iron-based catalyst, a cobalt-based catalyst or a ruthenium-based catalyst; more preferably, the waste supported metal catalyst comprises one or more of a waste methanol synthesis catalyst, a waste hydrogenation catalyst or a waste hydrocracking catalyst; preferably, the mass concentration of the metal salt solution is 0.01wt%-3wt%; more preferably, the mass concentration of the metal salt solution is 0.5wt%-2.5wt%.

[0009] Further, the first acid solution includes a nitric acid solution; preferably, the mass concentration of nitric acid in the first acid solution is 3wt%-30wt%; more preferably, the mass concentration of nitric acid in the first acid solution is 5wt%-25wt%.

[0010] Furthermore, before the impurity removal calcination, the first oxide is first ground to 100-500 mesh; preferably, the impurity removal calcination temperature is 600°C-900°C; more preferably, the impurity removal calcination temperature is 600°C-800°C; preferably, the impurity removal calcination time is 120-480min.

[0011] Furthermore, the temperature of ion exchange is 60-100°C; preferably, the temperature of ion exchange is 80-100°C; preferably, the time of ion exchange is 1-6h; preferably, the solid-liquid ratio of FAU molecular sieve to metal salt solution is 1:0.5~-10g / mL, more preferably, the solid-liquid ratio of FAU molecular sieve to metal salt solution is 1:0.5~-7g / mL.

[0012] Furthermore, the molar ratio of each component in the composite FAU molecular sieve is: alumina: silica = 1: 0.5-10; alumina: MOH = 1: 5-30; alumina: water = 1: 10-80; alumina: acid metal salt = 1: 0.5-20; alumina: MO = 1: 0.2-5; MO is the oxide of the active metal in the composite FAU molecular sieve, and MOH is the hydroxide of the active metal in the composite FAU molecular sieve; the active metal includes: two or more active metals of Fe, K, Cu, Mn or Zn.

[0013] Further, the preparation method of FAU molecular sieve comprises: a) mixing an aluminum source gel system and a silicon source gel system to obtain a gel solution; b) mixing the gel solution with a first alkali source to obtain a gel slurry solution; c) subjecting the gel slurry solution to a first crystallization reaction and a second crystallization reaction to obtain a molecular sieve seed solution; d) mixing an aluminum-containing solution, a silicon-containing solution and a molecular sieve seed solution to obtain a FAU molecular sieve; preferably, d) comprises da) or db), da) comprises: mixing an aluminum-containing solution and a silicon-containing solution to obtain Gel mother liquor; then mixing the gel mother liquor with a molecular sieve seed solution, performing a first aging reaction and a third crystallization reaction to obtain a FAU molecular sieve; db) comprising: mixing and extruding an aluminum-containing solution, a silicon-containing solution, a molecular sieve seed solution and auxiliary materials to obtain a molecular sieve precursor; then sequentially performing a second aging reaction and a fourth crystallization reaction on the molecular sieve precursor to obtain a FAU molecular sieve; preferably, the auxiliary materials include one or more of a molding agent, a pore-forming agent or a lubricant; preferably, the auxiliary materials account for 2 to 15 wt% of the mass of the molecular sieve precursor.

[0014] Furthermore, the preparation method includes: first, using a), b), c) and da) to prepare FAU molecular sieve; secondly, mixing the FAU molecular sieve with a metal salt solution and performing ion exchange to obtain a composite FAU molecular sieve; then mixing the composite FAU molecular sieve with auxiliary materials, drying and performing a first calcination to obtain a metal-modified molecular sieve; or first, using a), b), c) and db) to prepare FAU molecular sieve; secondly, mixing the FAU molecular sieve with a metal salt solution and performing ion exchange to obtain a composite FAU molecular sieve; then drying and performing a first calcination on the composite FAU molecular sieve in sequence to obtain a metal-modified molecular sieve; preferably, the mass ratio of the composite FAU molecular sieve to the forming agent, the pore-forming agent and the lubricant is: 5-95: 5-95: 0.05-5: 0.01-5; preferably, the drying temperature is 80-150°C; preferably, the drying time is 0.1-5h.

[0015] Further, da) also includes: mixing the second oxide and the second alkali source in a mass ratio of 1:0.5-1:5 for a third calcination to obtain a third calcination product; using a second acid solution to dissolve and filter the third calcination product to obtain an aluminum-containing solution and a filter residue; mixing the filter residue, the third alkali source and water in a mass ratio of 100:60:400, filtering to obtain a silicon-containing solution; mixing the silicon-containing solution with the aluminum-containing solution to obtain a gel mother liquor; preferably, the temperature of the third calcination is 550°C-800°C, and the time is 60-120min; preferably, the molar ratio of the components of the gel mother liquor is: silicon dioxide: aluminum oxide = 0.5-6.0:1, sodium oxide: silicon dioxide = 0.5-6.0:1, water: silicon dioxide = 10-100:1; preferably, the second alkali source includes sodium hydroxide, sodium carbonate, calcium hydroxide, Preferably, the third alkali source includes one or more of sodium hydroxide, sodium carbonate, calcium hydroxide, potassium hydroxide or ammonia water; Preferably, the second acid solution includes one or more of nitric acid, hydrochloric acid, sulfuric acid, phosphoric acid, citric acid, acetic acid; Preferably, the concentration of the second acid solution is 10wt%-35wt%, including but not limited to 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, 15wt%, 16wt%, 17wt%, 18wt%, 19wt%, 20wt%, 21wt%, 22wt%, 23wt%, 24wt%, 25wt%, 26wt%, 27wt%, 28wt%, 29wt%, 30wt%, 31wt%, 32wt%, 33wt%, 34wt% or 35wt%.

[0016] Further, the second oxide includes any one or more of the following oxides: Fe, Al, Si or Ca; preferably, the second oxide includes a waste catalyst; preferably, the waste catalyst includes one or more of a waste ZSM-5 molecular sieve catalyst, a waste MTO catalyst, a waste FAU type molecular sieve, fly ash, a waste A type molecular sieve, a waste FCC catalyst or a waste VOC adsorbent.

[0017] Further, preferably, in a), the preparation method of the aluminum source gel system is: uniformly mix the aluminum source and water, stir at 20-60°C for 0.1-12h, and maintain the stirring speed at 200-800rpm to obtain the aluminum source gel system; preferably, the aluminum source includes one or more of sodium aluminate, pseudo-boehmite, aluminum sulfate or aluminum nitrate; preferably, in a), the preparation method of the silicon source gel system is: uniformly mix the silicon source and water, stir at 20-60°C for 0.1-12h, and maintain the stirring speed at 200-800rpm to obtain the silicon source gel system; preferably, the silicon source includes silica sol, ortho- One or more of ethyl silicate, coarse-pore silica gel, silicon powder, fly ash or carbon black; preferably, in b), the pH value of the gel slurry solution is 8.5-12.5; preferably, the first alkali source includes one or more of sodium hydroxide, sodium carbonate, calcium hydroxide, potassium hydroxide or ammonia water; preferably, in c), the atomic ratio of each component in the FAU molecular sieve seed solution is silicon dioxide:alumina=0.02-5:1, sodium oxide:silicon dioxide=0.005-2.0:1, water:silicon dioxide=0.5-20:1; preferably, the FAU molecular sieve includes X-type molecular sieve or Y-type molecular sieve.

[0018] Further, in c), the time of the first crystallization reaction is 4-24h, and the temperature is 20-60°C; preferably, the time of the second crystallization reaction is 6-48h, and the temperature is 60-100°C; preferably, in e), the time of the aging reaction is 0.1-24h, and the temperature is 20-100°C; preferably, the time of the third crystallization reaction is 0.1-36h, and the temperature is 60-105°C. Preferably, in da), the time of the first aging reaction is 0.1-24h, and the temperature is 20-100°C; preferably, the time of the third crystallization reaction is 0.1-36h, and the temperature is 60-105°C; the time of the second aging reaction is 0.1-24h, and the temperature is 20-100°C, and the time of the fourth crystallization reaction is 0.1-36h, and the temperature is 60-105°C.

[0019] In order to achieve the above object, according to a second aspect of the present invention, a metal-modified molecular sieve is provided. The metal-modified molecular sieve is prepared by the above-mentioned method for preparing a metal-modified molecular sieve.

[0020] To achieve the above objectives, according to the third aspect of the present invention, there is provided a metal-modified molecular sieve prepared by any of the above-mentioned methods for preparing metal-modified molecular sieves, or the use of the above-mentioned metal-modified molecular sieves in adsorbing oxygen-containing compounds in hydrocarbon compounds.

[0021] By applying the technical solution of the present invention, a salt solution containing two or more metal elements of Fe, K, Cu, Mn or Zn is mixed with a FAU molecular sieve, and at least two metal elements in the metal salt solution are loaded onto the FAU molecular sieve to obtain a composite FAU molecular sieve; after the composite FAU molecular sieve is mixed with auxiliary materials, a first calcination is performed, which can further promote its stable molding, and a variety of active metals can be stably loaded in the pores of the molecular sieve adsorbent, thereby increasing the single-pass adsorption capacity of the molecular sieve adsorbent. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0023] Figure 1 A schematic diagram of the XRD diffraction results of the metal-modified FAU molecular sieve according to Example 1 of the present invention is shown.

[0024] Figure 2 A schematic diagram of the SEM characterization results of the metal-modified FAU molecular sieve according to Example 1 of the present invention is shown.

[0025] Figure 3 A schematic diagram of the SEM characterization results of the metal-modified FAU molecular sieve according to Example 2 of the present invention is shown.

[0026] Figure 4 A schematic diagram of the SEM characterization results of the metal-modified FAU molecular sieve according to Example 7 of the present invention is shown. DETAILED DESCRIPTION

[0027] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.

[0028] As mentioned in the background technology, molecular sieve adsorbents have limited single-pass adsorption capacity and require frequent regeneration due to the limitations of the preparation methods in the prior art. In addition, in actual industrial production, there will be disadvantages such as the need for frequent activation. Therefore, in this application, the inventors attempt to develop a new molecular sieve adsorbent and a preparation method thereof. After the FAU molecular sieve is modified with a composite metal substance, a molecular sieve adsorbent with a large single-pass adsorption capacity and excellent performance can be obtained, and thus a series of protection schemes of this application are proposed.

[0029] In a first typical embodiment of the present application, a method for preparing a metal-modified molecular sieve is provided, the preparation method comprising: I) mixing a FAU molecular sieve with a metal salt solution and performing ion exchange to obtain a composite FAU molecular sieve, wherein the metal salt solution is a salt solution containing two or more metal elements selected from Fe, K, Cu, Mn or Zn; II) performing a first calcination on the composite FAU molecular sieve to obtain a metal-modified molecular sieve.

[0030] The adsorbents currently prepared for deep removal of oxygenated compound impurities in coal chemical industry are mainly based on a single adsorption structure, and are mainly used to remove oxides in gaseous form. Due to the huge differences in molecular weight and molecular structure of C4 and above hydrocarbon substances, the dynamic kinematic diameter, pore size and composition of liquid oxides are also different. Therefore, the adsorbents in the prior art cannot fully adapt to the wide variety of oxygenated compounds in C4 and above hydrocarbon substances. At present, in order to obtain this kind of molecular sieve adsorbent that can adsorb C4 and above hydrocarbon substances, most of them use single metal exchange or impregnation acid-base modification and other technologies in the preparation process to load active metal elements on the pores and adsorb the above-mentioned oxides, but due to the excessive and complex types of oxides, it is usually difficult to adsorb a wide variety of oxides by only loading a single active metal, so the effect is not good. If multiple active metal elements are loaded, several metal modifications need to be performed, but the steps of metal modification are many, the operation is difficult, resulting in excessively high preparation costs, and in the process of multiple modifications, some metal elements originally loaded on the pores will fall off. Therefore, the metal-modified molecular sieves prepared by the above method have poor modification effects, small single-pass adsorption amounts, and high modification process costs, making it difficult to meet the growing process requirements.

[0031] In the present application, a salt solution of two or more metal elements in Fe, K, Cu, Mn or Zn is ion exchanged with a FAU molecular sieve to obtain a composite FAU molecular sieve. Further, the composite FAU molecular sieve is subjected to high-temperature roasting under hydrothermal conditions, and the above-mentioned multiple metal elements are fixed in the molecular sieve pores at one time, so that the multiple metal elements can be evenly distributed in the pores, not easy to fall during use, and stably formed. Moreover, under hydrothermal conditions, after high-temperature roasting, the pore size and crystal form of the molecular sieve can also be further regulated so that the pore diameter formed can selectively adsorb C4 and above hydrocarbon substances. The molecular sieve adsorbent prepared by the preparation method of the present application combines the advantages of the FAU molecular sieve, and through the metal modification method in the present application, it is possible to stably load multiple metal elements in the molecular sieve at one time, reducing the adsorption heat value of the molecular sieve adsorbent, prompting the molecular sieve adsorbent of the present application to have a higher thermal stability, and the adsorption performance is further optimized. Moreover, the various metal elements loaded in the pores of the molecular sieve of the present application provide a variety of active sites, which can adsorb a wide variety of oxygen-containing compounds in C4 and above hydrocarbon substances, have high adsorption efficiency, and a large single-pass adsorption amount, and can have a wider range of applications in the field of shape-selective adsorption.

[0032] In a preferred embodiment, the temperature of the first calcination is 400-650°C (including but not limited to 400°C, 450°C, 500°C, 550°C, 600°C or 650°C); preferably, the time of the first calcination is 1-6h (including but not limited to 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5 or 6h).

[0033] The present application accurately controls the temperature and time of the first roasting, and the molecular sieve framework structure undergoes rearrangement to form a more stable chemical bond, thereby further increasing the stability of the entire framework. And further, the pore structure of the pores loaded with various metal elements and the overall crystal form of the molecular sieve are properly regulated to make the pore structure more regular and uniform, so that the active metal loaded in the FAU molecular sieve pores is not easy to fall during use, forming a stable, higher adsorption activity and more selective FAU molecular sieve, further improving the single-pass adsorption capacity of the FAU molecular sieve. And roasting in the above-mentioned temperature range and time helps to improve the thermal stability of the molecular sieve, so that it is not easy to collapse and denature during high-temperature industrial applications, and the adsorption efficiency is higher.

[0034] In a preferred embodiment, the method for preparing the metal salt solution comprises: mixing a first oxide with a first acid solution to obtain a metal salt solution; preferably, the first oxide comprises a waste catalyst; preferably, the method for preparing the metal salt solution comprises: removing impurities from the waste catalyst by calcination, and then mixing it with the first acid solution to obtain a metal salt solution; preferably, the solid-liquid ratio of the first oxide to the first acid solution is 1:50-60 g / mL; preferably, the waste catalyst comprises one or more of a waste Fischer-Tropsch catalyst, a waste supported metal catalyst or a waste supported metal adsorbent; more preferably, the waste Fischer-Tropsch catalyst comprises one or more of an iron-based catalyst, a cobalt-based catalyst or a ruthenium-based catalyst; more preferably Preferably, the waste supported metal catalyst includes one or more of a waste methanol synthesis catalyst, a waste hydrogenation catalyst or a waste hydrocracking catalyst; preferably, the mass concentration of the metal salt solution is 0.01wt%-3wt% (including but not limited to 0.01wt%, 0.02wt%, 0.05wt%, 0.08wt%, 0.1wt%, 0.15wt%, 2wt%, 2.1wt%, 2.2wt%, 2.3wt%, 2.4wt%, 2.5wt%, 2.6wt%, 2.7wt%, 2.8wt%, 2.9wt% or 3wt%); more preferably, the mass concentration of the metal salt solution is 0.5wt%-2.5wt%.

[0035] In the present application, the first oxide is mixed with the first acid solution to obtain a metal salt solution rich in metal ions and acid radical ions; the metal salt solution containing the acid radical solution is mixed with the FAU molecular sieve to perform ion exchange, thereby changing the polarity of the original molecular sieve and loading a variety of active metal elements onto the FAU molecular sieve at one time, thereby obtaining a FAU molecular sieve compounded with a variety of metal elements, so that it can adsorb C4 and above hydrocarbon substances.

[0036] The first oxide in the present application is derived from waste catalysts, which refer to discarded catalysts that have exceeded their normal service life, have a catalytic activity that is 30% lower than that of new catalysts or have no catalytic performance, and cannot be regenerated. The present application uses waste catalysts as the first oxide, and first pre-treats the waste catalysts (removes impurities and roasts) to remove residual impurities in the waste catalysts. The waste catalysts after impurities removal are mixed with an acid solution to obtain a metal salt solution rich in multiple metal ions in the present application.

[0037] By controlling the metal salt solution within the above range, the compatibility of the metal salt solution with the FAU molecular sieve is improved, so that a variety of active metal elements can be further loaded into the molecular sieve pores to improve the adsorption performance of the molecular sieve adsorbent, so that the polarity of the molecular sieve changes, the adsorption heat value of the molecular sieve adsorbent is reduced, and it has a higher hydrothermal stability. Moreover, compared with other metal oxides, the waste catalyst of the present application is low in cost, more environmentally friendly, rich in metal types, and has better compatibility with the molecular sieve to be modified. Utilizing the preparation method of the present application, it is possible to stably load a variety of metal ions into the molecular sieve pores at one time, and a FAU molecular sieve with a composite of multiple metal active elements can be formed without multiple modifications. The single-pass adsorption capacity is large, the selective adsorption capacity is strong, the adsorption efficiency is high, and it is more suitable for industrial scale-up production. It is suitable for adsorbing a wide variety of oxygen-containing compounds in C4 and C4 hydrocarbons, and has a wider range of applications in the field of shape-selective adsorption.

[0038] In a preferred embodiment, in S1), the first acid solution comprises a nitric acid solution; preferably, the mass concentration of nitric acid in the first acid solution is 3wt%-30wt%, including but not limited to 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, 15wt%, 16wt%, 17wt%, 18wt%, 19wt%, 18wt%, 19wt%, 20wt%, 21wt%, 22wt%, 23wt%, 24wt%, 25wt%, 26wt%, 27wt%, 28wt%, 29wt% and 30wt%; more preferably, the mass concentration of nitric acid in the first acid solution is 5wt%-25wt%.

[0039] The present application controls the nitric acid solution within the above range so that it can be better mixed with the waste catalyst (first oxide), thereby promoting the formation of the metal salt solution of the present application, which is beneficial to the subsequent loading of multiple metal ions in the molecular sieve channels and promoting the formation of the molecular sieve adsorbent of the present application.

[0040] In a preferred embodiment, S1) includes: first grinding the first oxide to 100-500 mesh and then performing impurity removal calcination; 100-500 mesh includes but is not limited to 100, 150, 200, 250, 300, 350, 400, 450 or 500 mesh, and performing the first calcination; preferably, the impurity removal calcination temperature is 600℃-900℃; including but not limited to 600℃, 650℃, 700℃, 750℃, 800℃, 850℃ or 900℃; more preferably, the impurity removal calcination temperature is 600℃-800℃; preferably, the first calcination time is 120-480min, including but not limited to 120, 130, 140, 150, 160, 170, 180, 190, 200, 210, 220, 230, 240, 250, 360 or 480min.

[0041] The present application performs impurity removal and roasting treatment on the waste catalyst (first oxide) containing multiple metal ions, removes impurities from the waste catalyst to prevent excessive impurities from affecting the purity of the metal salt solution used for subsequent modification, and mixes the roasted product with the above-mentioned first acid solution and then filters it to remove the impurity filter residue to obtain the metal salt solution used for metal modification in the present application. Grinding the first oxide to the above-mentioned range is conducive to improving the effect of impurity removal and roasting, and can further control the particle size of the first oxide, so that the active metal elements therein can be better mixed with the acid solution to form a stable metal salt solution, and promote the subsequent metal modification of the FAU molecular sieve.

[0042] In a preferred embodiment, the temperature of ion exchange is 60-100°C, including but not limited to 60°C, 70°C, 80°C, 90°C or 100°C; more preferably, the temperature of ion exchange is 80-100°C; preferably, the time of ion exchange is 1-6h, including but not limited to 1, 2, 3, 4, 5 or 6h.

[0043] In a preferred embodiment, the molar ratio of each component in the composite FAU molecular sieve is: alumina: silicon dioxide = 1: 0.5-10 including but not limited to 1: 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10; alumina: MOH = 1: 5-30 (including but not limited to 1: 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30); alumina: water = 1: 10-80 (1: 10, 20, 30, 40 , 50, 60, 70 or 80); Alumina: acid metal salt = 1: 0.5-20 (including but not limited to 1: 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19 or 20); Alumina: MO = 1: 0.2-5 (1: 0.2, 1, 2, 3, 4 or 5); MO is the oxide of the active metal in the composite FAU molecular sieve, and MOH is the hydroxide of the active metal in the composite FAU molecular sieve; the active metal includes: two or more active metals of Fe, K, Cu, Mn or Zn.

[0044] The molar ratio of each component in the composite FAU molecular sieve is: alumina: silicon dioxide = 1: 0.5-10 (alumina: metal hydroxide = 1: 5-30; alumina: water = 1: 10-80; alumina: acid metal salt = 1: 0.5-20; alumina: metal oxide = 1: 0.2-5.

[0045] The present application mixes a metal salt solution with a FAU molecular sieve to cause ion exchange, which can improve the stability of the molecular sieve framework and increase the distribution of the molecular sieve active sites. By controlling the temperature and time of the ion exchange, the ion exchange can be promoted, the efficiency of the modified reaction can be improved, and the various metal elements in the metal salt solution can be better attached to the inside of the molecular sieve, so that the molecular sieve pores are rich in various active metal elements, the polarity of the molecular sieve is changed, and the thermal stability is further improved, and finally the adsorption of oxygen-containing compound impurities in C4 and C4 or higher raw materials can be formed.

[0046] In a preferred embodiment, the preparation method of FAU molecular sieve includes: a) mixing an aluminum source gel system and a silicon source gel system to obtain a gel solution; b) mixing the gel solution with a first alkali source to obtain a gel slurry solution; c) subjecting the gel slurry solution to a first crystallization reaction and a second crystallization reaction to obtain a molecular sieve seed solution; d) mixing an aluminum-containing solution, a silicon-containing solution and a molecular sieve seed solution to obtain a FAU molecular sieve; preferably, d) includes da) or db), da) includes: mixing an aluminum-containing solution and a silicon-containing solution , obtain a gel mother solution; then mix the gel mother solution with a molecular sieve seed solution, perform a first aging reaction and a third crystallization reaction, and obtain a FAU molecular sieve; db) comprises: mixing and extruding an aluminum-containing solution, a silicon-containing solution, a molecular sieve seed solution, and auxiliary materials to obtain a molecular sieve precursor; then sequentially performing a second aging reaction and a fourth crystallization reaction on the molecular sieve precursor to obtain a FAU molecular sieve; preferably, the auxiliary materials include one or more of a molding agent, a pore-forming agent, or a lubricant; preferably, the auxiliary materials account for 2-15wt% of the molecular sieve precursor mass. Preferably, the molding agent includes one or more of kaolin, high white mud, bentonite, montmorillonite, talc, or clay; preferably, the pore-forming agent includes one or more of sesbania powder, gum arabic, lignin, guar gum, or ethyl cellulose; preferably, the lubricant includes one or more of vegetable oil, glycerol, base oil, or silicone oil; preferably, the aluminum-containing solution and the silicon-containing solution are derived from waste catalysts.

[0047] In a preferred embodiment, the preparation method comprises: first, using a), b), c) and da) to prepare FAU molecular sieve; secondly, mixing the FAU molecular sieve with a metal salt solution and performing ion exchange to obtain a composite FAU molecular sieve; then mixing the composite FAU molecular sieve with an auxiliary material, drying and performing a first calcination to obtain a metal-modified molecular sieve; or first, using a), b), c) and db) to prepare FAU molecular sieve; secondly, mixing the FAU molecular sieve with a metal salt solution and performing ion exchange to obtain a composite FAU molecular sieve; then mixing the composite FAU molecular sieve with an auxiliary material, drying and performing a first calcination to obtain a metal-modified molecular sieve. The composite FAU molecular sieve is dried and first calcined in sequence to obtain a metal-modified molecular sieve; preferably, the mass ratio of the composite FAU molecular sieve to the forming agent, the pore-forming agent and the lubricant is: 5-95: 5-95: 0.05-5: 0.01-5; preferably, the drying temperature is 80-150°C (including but not limited to 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C or 150°C); preferably, the drying time is 0.1-5h (including but not limited to 0.1, 0.5, 1, 2, 3, 4 or 5h).

[0048] In a preferred embodiment, S3-2) includes: using the FAU molecular sieve obtained in db), after ion exchange in S2), to obtain a composite FAU molecular sieve; mixing the composite FAU molecular sieve with auxiliary materials, and drying and first calcining in sequence; preferably, the auxiliary materials include one or more of a forming agent, a pore-forming agent or a lubricant; preferably, the mass ratio of the composite FAU molecular sieve and the forming agent, the pore-forming agent and the lubricant is: 5-95:5-95:0.05-5:0.01-5; preferably, the drying temperature is 80-150°C; preferably, the drying time is 0.1-5h; preferably, the temperature of the first calcination is 400-650°C; preferably, the time of the first calcination is 0.1-5h.

[0049] In this application, there are different strategies for the participation of functional excipients in the preparation of molecular sieves. The first is to directly mix the silicon-containing solution and the aluminum-containing solution to obtain a gel mother liquor when preparing the FAU molecular sieve, and directly mix the gel mother liquor with the molecular sieve seed solution for aging and crystallization reaction to obtain the FAU molecular sieve. The FAU molecular sieve prepared by this scheme is mixed with the excipients during the metal modification process and then dried and calcined for the first time. In this step, the molecular sieve is further shaped and pore-formed to further increase the specific surface area and pore volume of the final metal-modified molecular sieve.

[0050] The second method is to extrude the molecular sieve seed solution containing aluminum and silicon in the process of preparing the FAU molecular sieve, and obtain a molecular sieve precursor with mesopores and micropores, and further increased specific surface area and pore volume; adjust the pH of the hydrothermal crystallization reaction to 6.5-8 with an alkaline solution, and perform the same aging reaction and crystallization reaction to obtain the FAU molecular sieve, and no auxiliary materials are added in the subsequent metal modification process. Those skilled in the art can choose different auxiliary material addition strategies according to actual needs.

[0051] The present application controls the drying temperature and time so that the composite FAU molecular sieve can be fully dried without changing its properties, which is beneficial to promoting the effect of the subsequent first roasting. In a preferred embodiment, da) further comprises: mixing the second oxide and the second alkali source in a mass ratio of 1:0.5-5 (including but not limited to 1:0.5, 1, 2, 3, 4 or 5) for a third calcination to obtain a third calcined product; using a second acid solution to dissolve and filter the third calcined product to obtain an aluminum-containing solution and a filter residue; mixing the filter residue, the third alkali source and water in a mass ratio of 100:60:400, and filtering to obtain a silicon-containing solution; mixing the silicon-containing solution with the aluminum-containing solution to obtain a gel mother liquor; preferably, the temperature of the third calcination is 550°C-800°C, and the time is 60-120min; preferably, the molar ratio of the components of the gel mother liquor is: silicon dioxide: aluminum oxide = 0.5-6.0:1, sodium oxide: silicon dioxide = 0.5-6.0:1, water: silicon dioxide = 10-100:1; preferably, the second alkali source comprises hydroxide Preferably, the third alkali source includes one or more of sodium hydroxide, sodium carbonate, calcium hydroxide, potassium hydroxide or ammonia water; Preferably, the second acid solution includes one or more of nitric acid, hydrochloric acid, sulfuric acid, phosphoric acid, citric acid, acetic acid; Preferably, the concentration of the second acid solution is 10wt%-35wt%, including but not limited to 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, 15wt%, 16wt%, 17wt%, 18wt%, 19wt%, 20wt%, 21wt%, 22wt%, 23wt%, 24wt%, 25wt%, 26wt%, 27wt%, 28wt%, 29wt%, 30wt%, 31wt%, 32wt%, 33wt%, 34wt% or 35wt%.

[0052] In a preferred embodiment, the second oxide comprises any one or more of the following oxides: Fe, Al, Si or Ca; preferably, the second oxide comprises a waste catalyst; preferably, the waste catalyst comprises one or more of a waste ZSM-5 molecular sieve catalyst, a waste MTO catalyst, a waste X-type molecular sieve, fly ash, a waste A-type molecular sieve, a waste FCC catalyst, a waste Y-type molecular sieve or a waste VOC adsorbent.

[0053] In a preferred embodiment, in the preparation method of FAU molecular sieve, in the above a), the preparation method of the aluminum source gel system is: uniformly mix the aluminum source and water, stir at 20-60°C for 0.1-12h, and maintain the stirring speed at 200-800rpm to obtain the aluminum source gel system; preferably, the aluminum source includes one or more of sodium aluminate, pseudo-boehmite, aluminum sulfate, and aluminum nitrate; preferably, in a), the preparation method of the silicon source gel system is: uniformly mix the silicon source and water, stir at 20-60°C for 0.1-12h, and maintain the stirring speed at 200-800rpm to obtain the silicon source gel system; preferably, the silicon source includes one or more of silica sol, tetraethyl orthosilicate, macroporous silica gel, silicon powder, fly ash, and carbon black; preferably, in b), the gel The pH value of the slurry solution is 8.5-12.5, including but not limited to 8.5, 9.5, 10.5, 11.5 or 12.5; preferably, the first alkali source includes one or more of sodium hydroxide, sodium carbonate, calcium hydroxide, potassium hydroxide or ammonia water; preferably, in c), the molar ratio of each component in the FAU molecular sieve seed solution is silicon dioxide: aluminum oxide = 0.01-2.5:1, sodium oxide: silicon dioxide = 0.01-4.0:1, water: silicon dioxide = 1.0-40.0:1; preferably, the FAU molecular sieve includes X-type molecular sieve and Y-type molecular sieve; preferably, the X-type molecular sieve includes but is not limited to 13X molecular sieve and 10X molecular sieve; preferably, the Y-type molecular sieve includes but is not limited to NaY molecular sieve and USY molecular sieve.

[0054] The present application utilizes inorganic waste as raw materials for silicon-containing solution and aluminum-containing solution, i.e., the above-mentioned second oxide, controls the pH value of the gel slurry solution, and performs segmented crystallization treatment, so as to obtain a FAU molecular sieve with a smooth crystal surface without impurities and a high conversion rate. Different types of FAU molecular sieves have different crystal structures of silicates. The present application can control the silicon-aluminum ratio of the molecular sieve by controlling the ratio, crystallization temperature and crystallization time in the raw materials, and obtain FAU molecular sieves of different crystal forms. By using the FAU molecular sieve and then performing metal modification with the above-mentioned first oxide containing metal oxide, a FAU molecular sieve adsorbent with an enlarged surface area and pore volume, high polarity, and improved adsorption performance can be obtained.

[0055] In a preferred embodiment, in c), the time of the first crystallization reaction is 4-24h, including but not limited to 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23 or 24h, and the temperature is 20-60°C, including but not limited to 20°C, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C or 60°C; preferably, the time of the second crystallization reaction is 6-48h, including but not limited to 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 30, 36, 40 or 48h, and the temperature is 60-100°C, including but not limited to 60°C, 70°C, 80°C, 90°C or 100°C;

[0056] Preferably, in da), the time of the first aging reaction is 0.1-24h, including but not limited to 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23 or 24h, and the temperature is 20-100°C, including but not limited to 20°C, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C or 100°C; the time of the third crystallization reaction is 0.1-3 , 0.6, 0.7, 0.8, 0.9, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35 or 36 hours at a temperature of 60-105°C, including but not limited to 60°C, 70°C, 80°C, 90°C, 100°C, 101°C, 102°C, 103°C, 104°C or 105°C. Preferably, in db), the time of the second aging reaction is 0.1-24h, including but not limited to 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23 or 24h, and the temperature is 20-100°C, including but not limited to 20°C, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C or 100°C; the time of the fourth crystallization reaction is 0.1-3 , 0.6, 0.7, 0.8, 0.9, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35 or 36 hours at a temperature of 60-105°C, including but not limited to 60°C, 70°C, 80°C, 90°C, 100°C, 101°C, 102°C, 103°C, 104°C or 105°C.

[0057] In a second typical embodiment of the present application, a molecular sieve adsorbent is provided. The molecular sieve adsorbent is prepared by any of the above-mentioned methods for preparing the molecular sieve adsorbent.

[0058] In a third typical embodiment of the present application, there is provided a metal-modified molecular sieve prepared by any of the above-mentioned methods for preparing metal-modified molecular sieves, or the use of the above-mentioned metal-modified molecular sieves in adsorbing oxygen-containing compounds in hydrocarbon compounds.

[0059] The beneficial effects of the present application will be further explained in detail below in conjunction with specific embodiments.

[0060] Unless otherwise specified, the reagents in the examples and comparative examples of this application are conventional commercially available products.

[0061] Example 1

[0062] 1. Dissolve 18.0 g of silica sol in 18.0 g of deionized water in a closed reactor at 25°C and 500 rpm for 1 hour to obtain a silicon source gel system.

[0063] Dissolve 6.557 g of aluminum sulfate in 18.0 g of deionized water, stir at 25°C, at a rotation speed of 500 rpm, for 1 hour to obtain an aluminum source gel system; slowly add the aluminum source aqueous solution to the silicon source aqueous solution, and continue stirring at 60°C for 12 hours to obtain a gel solution.

[0064] 2. Dissolve 14g of sodium hydroxide in 36g of deionized water dispersion and add it to the gel solution. Control the pH value to maintain at 12.0. The obtained gel slurry solution is placed in a hydrothermal reactor for two-stage temperature-controlled crystallization. The first crystallization reaction temperature is 40°C and the time is 12h. The second crystallization reaction temperature is 95°C and the time is 24h to obtain a white seed solution.

[0065] 3. Mix 10g of 200-mesh waste ZSM-5 molecular sieve catalyst and 8g of 10% NaCO3 evenly, calcine at 650°C for 120min, and then dissolve and filter the calcined product with 25wt% nitric acid solution to obtain an aluminum-containing solution for standby use.

[0066] 10 g of filter residue was obtained by filtration, and 6 g of NaOH and 40 g of H2O were mixed and evenly filtered to obtain a silicon-containing solution. Finally, the silicon-containing solution and the aluminum-containing solution were mixed at a mass ratio of 4:1 to obtain a gel mother solution.

[0067] 4. Add 25 g of molecular sieve seed solution to the gel mother liquor and continue stirring and aging at 60°C for 12 hours. Perform a hydrothermal reaction and perform the third crystallization reaction at a crystallization temperature of 98°C for 24 hours. Filter and wash the reaction product, adjust the pH to 7, and dry it at 90°C to obtain the FAU molecular sieve.

[0068] The XRD diffraction (X-ray diffraction) diagram of the FAU molecular sieve of this embodiment is shown in FIG. Figure 1As shown, SEM (Scanning Electron Microscope, scanning electron microscope) characterization is as follows Figure 2 shown.

[0069] 5. Metal modification

[0070] S1) 2.0 g of 200-mesh waste methanol synthesis catalyst (with a metal copper loading of 1.2%, a metal zinc loading of 0.5%, and a metal iron loading of 0.05%) was calcined at 650° C. for 360 min, and a 15 wt % nitric acid solution was mixed with the calcined product and then filtered, with a solid-liquid ratio of 1:50; a 2.0 wt % metal salt solution was obtained;

[0071] S2) using 2.0wt% metal salt solution and 20g FAU molecular sieve to carry out ion exchange (loading) for 4h under hydrothermal conditions of 80°C, with a solid-liquid ratio of 1:7 to obtain a composite Cu-Zn-Fe-FAU molecular sieve.

[0072] The molar ratio of each component in the composite Cu-Zn-Fe-FAU molecular sieve is: SiO2 (derived from silicon source): Al2O3 in aluminum source (derived from aluminum source): MOH (metal hydroxide): H2O: MX (acid metal salt): metal oxide = 2.3: 1: 6.5: 40: 1.5: 1.5. In the present application, MOH is metal hydroxide, MX is acid metal salt, M is a general term for metal atoms, and X is a general term for acid ions.

[0073] S3) The composite Cu-Zn-Fe-FAU molecular sieve is mixed with clay in a mass ratio of 8.8:1.2, and then sesbania powder and glycerol are added to obtain a mixed system, in which the mass proportion of sesbania powder in the mixed system is 0.35%, and the mass proportion of glycerol is 0.15%. The above mixed system is extruded (rolled) into strips, dried at 90°C for 4h, and calcined at 500°C for 6h to obtain a metal-modified FAU molecular sieve adsorbent.

[0074] Example 2

[0075] Steps 1-2 are consistent with those in Example 1, and the other steps are specifically as follows:

[0076] 3. Mix 12g of 200-mesh waste 13X adsorbent and 10g of 15wt% NaCO3 evenly and calcine at 650°C for 120min. Then, use 15wt% nitric acid solution to dissolve and filter the calcined product to obtain an aluminum-containing solution for standby use.

[0077] 15 g of filter residue was obtained by filtration, and 6 g of NaOH and 40 g of H2O were uniformly mixed therewith and filtered to obtain a silicon-containing solution. Finally, the silicon-containing solution and the aluminum-containing solution were mixed at a mass ratio of 3.5:1 to obtain a gel mother solution.

[0078] 4. Add 15 g of the molecular sieve seed solution to the gel mother liquor and continue stirring and aging at 60° C. for 12 h, subject it to a hydrothermal reaction, and conduct a third crystallization reaction at a crystallization temperature of 95° C. for 24 h. Filter and wash the reaction product, adjust the pH to 7, and dry it at 90° C. to obtain a FAU molecular sieve. The SEM characterization of the FAU molecular sieve is as follows: Figure 3 shown.

[0079] 5. Metal modification

[0080] S1) 2.0 g of 200 mesh waste methanol synthesis catalyst (metal copper loading of 1.2%, metal zinc loading of 0.5%, metal iron loading of 0.05%) was calcined at 600° C. for 380 min, and the calcined product was mixed with 10 wt % nitric acid solution and filtered, with a solid-liquid ratio of 1:50 to obtain a 2.0 wt % metal salt solution;

[0081] S2) Using 2.0 wt % metal salt solution and 20 g FAU molecular sieve for ion exchange (loading) at 80° C. for 4 h, the solid-liquid ratio is 1:7 to obtain a composite Cu-Zn-Fe-FAU molecular sieve.

[0082] The molar ratio of each component in the composite Cu-Zn-Fe-FAU molecular sieve is SiO2:Al2O3:MOH:H2O:MX:metal oxide=4.5:1:15:40:2.5:1.5.

[0083] S3) The composite Cu-Zn-Fe-FAU molecular sieve was mixed with clay in a mass ratio of 8.2:1.8, and then gum arabic and PAO-4 were added to obtain a mixed system, in which the mass proportion of gum arabic in the mixed system was 1.5%, and the mass proportion of PAO-4 was 0.75%. The mixed system was formed by extrusion (rolling ball), dried at 90°C for 4h, and calcined at 500°C for 5h to obtain a metal-modified FUA molecular sieve adsorbent.

[0084] Example 3

[0085] Steps 1-4 are consistent with those in Example 1, and the other steps are specifically as follows:

[0086] 5. Metal modification

[0087] S1) 1.0 g of 300-mesh waste iron-based catalyst (metal iron loading of 0.75%, metal potassium loading of 0.25%, and metal manganese loading of 0.01%) was calcined at 700° C. for 300 min, and the calcined product was mixed with an 8 wt % nitric acid solution sample and filtered, with a solid-liquid ratio of 1:50 to obtain a metal salt solution;

[0088] S2) using 1.0% metal salt solution to mix with 20g FAU molecular sieve under hydrothermal conditions at 90°C for ion exchange (loading) for 3h, with a solid-liquid ratio of 1:7, to obtain a composite Fe-K-Mn-FAU molecular sieve.

[0089] The molar ratio of each component in the composite Fe-K-Mn-FAU molecular sieve is SiO2:Al2O3:MOH:H2O:MX:metal oxide=2.1:1:10:25:1.5:1.5.

[0090] S3) The composite Fe-K-Mn-FAU molecular sieve was mixed with clay in a mass ratio of 7.8:2.2, and then gum arabic and PAO-6 were added to obtain a mixed system, in which the mass proportion of gum arabic in the mixed system was 2.5%, and the mass proportion of PAO-6 was 0.45%. The mixed system was extruded (rolled) into a ball, dried at 120°C for 2h, and calcined at 450°C for 5h to obtain a metal-modified FUA molecular sieve adsorbent.

[0091] Example 4

[0092] Steps 1-4 are consistent with those in Example 1, and the other steps are specifically as follows:

[0093] 5. Metal modification

[0094] S1) 2.0 g of 300 mesh waste iron-based catalyst (metal iron loading of 1.25%, metal potassium loading of 0.75%, metal manganese loading of 0.02%) was calcined at 650° C. for 360 min, and the calcined product was mixed with 15 wt % nitric acid solution and filtered, with a solid-liquid ratio of 1:50 to obtain a 1.5 wt % metal salt solution;

[0095] S2) Using 1.5wt% metal salt solution and 20g FAU molecular sieve for ion exchange (loading) at 70°C for 5h at a solid-liquid ratio of 1:7 to obtain a composite Fe-K-Mn-FAU molecular sieve.

[0096] The molar ratio of each component in the composite FAU molecular sieve is SiO2:Al2O3:MOH:H2O:MX:metal oxide=3.0:1:25:35:4.5:1.5.

[0097] S3) The composite Fe-K-Mn-FAU molecular sieve was mixed with pseudo-boehmite at a mass ratio of 8.5:1.5, and then sesbania powder and glycerol were added to obtain a mixed system, in which the mass proportion of sesbania powder in the mixed system was 0.75%, and the mass proportion of glycerol was 0.55%. The mixed system was formed by extrusion (rolling ball), dried at 100°C for 3h, and calcined at 550°C for 4.5h to obtain a metal-modified FUA molecular sieve adsorbent.

[0098] Example 5

[0099] 1. Mix 25g of 200-mesh waste FCC catalyst and 75g of the molecular sieve seed solution in Example 1, then add 3.5wt% sesbania powder, 3wt% white oil, and 3.5wt% nitric acid solution, mix well, extrude (roll ball) and form a molecular sieve precursor.

[0100] 2. The molecular sieve precursor and NaOH (4 mol / L) were hydrothermally crystallized at 90°C for 36 h at a solid-liquid ratio of 4:1, pH = 7, and dried at 90°C to obtain FAU molecular sieve.

[0101] 3. Metal modification

[0102] S1) calcining 1.0 g of 200-mesh waste methanol synthesis catalyst (with a metal copper loading of 0.5%, a metal zinc loading of 0.2%, and a metal iron loading of 0.025%) at 650° C. for 360 min, and mixing the calcined product with a 20 wt % nitric acid solution at a solid-liquid ratio of 1:50 to obtain a 1 wt % metal salt solution;

[0103] S2) 1 wt % metal salt solution was mixed with 20 g FAU molecular sieve under hydrothermal conditions at 80° C., with a solid-liquid ratio of 1:0.5, and ion exchange (loading) was performed for 6 h to obtain a composite Cu-Zn-Fe-FAU molecular sieve.

[0104] The molar ratio of each component in the composite Cu-Zn-Fe-FAU molecular sieve is SiO2:Al2O3:MOH:H2O:MX:metal oxide=1.5:1:7.5:25:12:1.

[0105] 4. The composite Cu-Zn-Fe-FAU molecular sieve was dried at 100°C for 3 h and calcined at 550°C for 4.5 h to obtain a metal-modified FAU molecular sieve adsorbent.

[0106] Example 6

[0107] 1. Mix 20g of 200-mesh waste ZSM-5 catalyst and 80g of the molecular sieve seed solution in Example 1, then add 2.5wt% lignin, 3wt% glycerol and 2.5wt% nitric acid solution, mix evenly and extrude (roll ball) to obtain a molecular sieve precursor.

[0108] 2. The molecular sieve precursor and NaOH (3.0 mol / L) were hydrothermally crystallized at 90°C for 36 h at a solid-liquid ratio of 3.5:1, with a pH of 7, and dried at 90°C to obtain FAU molecular sieve.

[0109] 3. Metal modification

[0110] S1) 2.0 g of 200-mesh waste methanol synthesis catalyst was calcined at 650° C. for 360 min, and the calcined product was mixed with a 20 wt % nitric acid solution and filtered, with a solid-liquid ratio of 1:60 to obtain a metal salt solution;

[0111] S2) 1.25 wt % metal salt solution was mixed with 20 g FAU molecular sieve under hydrothermal reaction conditions at 80° C., with a solid-liquid ratio of 1:0.75, and ion exchange (loading) was performed for 6 h to obtain a composite Cu-Zn-Fe-FAU molecular sieve.

[0112] The molar ratio of each component in the composite FAU molecular sieve is SiO2:Al2O3:MOH:H2O:MX:metal oxide=4.5:1:12.5:45:18:1.25.

[0113] 4. The composite Cu-Zn-Fe-FAU molecular sieve was dried at 90°C for 3.5 h and calcined at 650°C for 3.5 h to obtain a metal-modified FAU molecular sieve adsorbent.

[0114] Example 7

[0115] 1. Mix 25g of 250-mesh waste 13X adsorbent and 75g of the molecular sieve seed solution in Example 1, then add 3wt% methyl cellulose, 3wt% white oil, and 3.5wt% nitric acid solution, mix well, extrude (roll ball) to form a molecular sieve precursor.

[0116] 2. The molecular sieve precursor and NaOH (3.0 mol / L) were hydrothermally crystallized at 90°C for 36 h at a solid-liquid ratio of 3.5:1, and the pH was 7. The FAU molecular sieve was dried at 90°C. The SEM characterization of the FAU molecular sieve is as follows: Figure 4 shown.

[0117] 3. Metal modification

[0118] S1) Weighing 17.8 g of magnesium nitrate hexahydrate and 3.2 g of potassium nitrate respectively, mixing and dissolving them to prepare a 2 wt % metal salt solution;

[0119] S2) using a 2 wt % metal salt solution to perform ion exchange with 20 g of FAU molecular sieve under hydrothermal conditions at 80° C. for 3 h (load), with a solid-liquid ratio of 1:1, to obtain a composite Mg-K-FAU molecular sieve;

[0120] The molar ratio of each component in the composite Mg-K-FAU molecular sieve is SiO2:Al2O3:MOH:H2O:MX:metal oxide=2.5:1:25:60:15:1.

[0121] 4. The composite Mg-K-FAU molecular sieve was dried at 80°C for 2.5 h and calcined at 400°C for 5 h to obtain a metal-modified FAU molecular sieve adsorbent.

[0122] Example 8

[0123] The difference between this embodiment and embodiment 1 is that in the metal modification S2), the solid-liquid ratio of FAU molecular sieve to metal salt solution is 1:3, the concentration of the metal salt solution is 2.5 wt %, the ion exchange time is 2 h, and the temperature is 100° C.

[0124] Example 9

[0125] The difference between this embodiment and embodiment 1 is that in the metal modification S2), the solid-liquid ratio of FAU molecular sieve to metal salt solution is 1:4, the concentration of the metal salt solution is 2.75wt%, the ion exchange time is 5h, and the temperature is 75°C.

[0126] Example 10

[0127] The only difference between this embodiment and embodiment 1 is that the temperature of the first calcination in S3) in the metal modification is 350° C. and the time is 8 h.

[0128] Embodiment 11

[0129] The only difference between this embodiment and embodiment 1 is that the temperature of the first calcination in S3) in the metal modification is 700° C. and the time is 1.5 h.

[0130] Comparative Example 1

[0131] The difference between this example and Example 1 is that, in the metal modification, there is no S1), and the FAU molecular sieve is directly modified with a metal salt solution, and the metal salt solution of this comparative example is copper nitrate.

[0132] Comparative Example 2

[0133] The difference between this example and Example 1 is that, in the metal modification, there is no S1), and the FAU molecular sieve is directly modified with a metal salt solution, and the metal salt solution of this comparative example is ferric nitrate nonahydrate.

[0134] Comparative Example 3

[0135] The only difference between this comparative example and Example 1 is that in the metal modification, the second calcination in S3) is not performed after the ion exchange in S2), and the metal-modified FAU molecular sieve adsorbent is obtained directly after drying.

[0136] Comparative Example 4

[0137] Prior art molecular sieve adsorbents

[0138] The “molecular sieve adsorbent in the prior art” used in this application is 13X molecular sieve adsorbent, purchased from Tianjin Xijinna Environmental Protection Materials Technology Co., Ltd.

[0139] The metal-modified FUA molecular sieve adsorbent of the above-mentioned embodiment and the molecular sieve adsorbent in the prior art were tested for BET (Brunauer-Emmett-Teller) specific surface area, BJH (Barrett-Joyner-Halenda) adsorption average pore width, pore volume and single-pass adsorption capacity. The results are shown in Table 1 and Table 2, respectively.

[0140] Table 1

[0141]

[0142] Among them, micropores refer to pores with a pore diameter of less than 2 nm, and mesopores refer to pores with a pore diameter of 2 to 50 nm.

[0143] Single-pass adsorption capacity test method: dynamic adsorption is carried out in a fixed bed evaluation device with a filling capacity of 10-200g (Tianjin Pengxiang Technology Co., Ltd., article number: 20200706PX042). The C4-C5 hydrocarbon raw material containing oxygenated compound impurities is delivered to the adsorbent bed from bottom to top at a flow rate of 0.5-20mL / min through a metering pump. The reactor outlet material is collected and the mass concentration of the material is tested.

[0144] The calculation formula of single-pass adsorption capacity is as follows:

[0145]

[0146] Where: Q—adsorbent single-pass adsorption capacity, mg g -1 ;

[0147] C0—Material mass concentration at the initial moment, mg·L -1 ;

[0148] C e —Mass concentration of material when reaching equilibrium, mg·L -1 ;

[0149] V—volume of material solution, mL;

[0150] m—mass of adsorbent, g.

[0151] Table 2

[0152] FAU molecular sieve adsorbent Single-pass adsorption capacity Q (mg / g) Example 1 69.59 Example 2 64.32 Example 3 61.23 Example 4 58.58 Example 5 55.23 Example 6 50.47 Example 7 48.69 Example 8 44.52 Example 9 42.25 Example 10 41.33 Embodiment 11 39.05 Comparative Example 1 38.22 Comparative Example 2 36.75 Comparative Example 3 35.14 Comparative Example 4 30.42

[0153] The elemental compositions of the spent catalyst and spent adsorbent in the first oxide and the second oxide used in the above examples are shown in Table 3.

[0154] Table 3

[0155]

[0156]

[0157] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those described herein, for example.

[0158] From the above description, it can be seen that the above-mentioned embodiments of the present invention achieve the following technical effects: using the preparation method of the molecular sieve adsorbent of the present application, by using inorganic waste as raw material to prepare FAU molecular sieve, and then using inorganic waste containing metal oxides to perform metal modification on it, a composite metal molecular sieve adsorbent can be finally obtained. The surface area, pore volume and adsorption performance of the molecular sieve adsorbent are improved, and the raw material conversion rate is high. Compared with the preparation method of the prior art, the cost is low, the preparation method is simple, and the adsorption performance of the obtained molecular sieve adsorbent is good, which solves the problem that the molecular sieve adsorbent in the prior art needs to be frequently regenerated when used.

[0159] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a metal-modified molecular sieve, characterized in that: The preparation method comprises: 1) mixing the FAU molecular sieve with a metal salt solution and performing ion exchange to obtain a composite FAU molecular sieve, wherein the metal salt solution is a salt solution containing two or more metal elements selected from Fe, K, Cu, Mn or Zn; II) performing a first calcination on the composite FAU molecular sieve to obtain the metal-modified molecular sieve.

2. The preparation method according to claim 1, characterized in that: The temperature of the first calcination is 400-650°C; Preferably, the first calcination time is 1-6 hours.

3. The preparation method according to claim 1, characterized in that: The method for preparing the metal salt solution comprises: mixing a first oxide with a first acid solution to obtain the metal salt solution; Preferably, the first oxide comprises spent catalyst; Preferably, the method for preparing the metal salt solution comprises: removing impurities and calcining the waste catalyst, and then mixing the waste catalyst with the first acid solution to obtain the metal salt solution; Preferably, the solid-to-liquid ratio of the first oxide to the first acid solution is 1:50-60 g / mL; Preferably, the spent catalyst comprises one or more of a spent Fischer-Tropsch catalyst, a spent supported metal catalyst or a spent supported metal adsorbent; More preferably, the waste Fischer-Tropsch catalyst comprises one or more of an iron-based catalyst, a cobalt-based catalyst or a ruthenium-based catalyst; More preferably, the waste supported metal catalyst comprises one or more of a waste methanol synthesis catalyst, a waste hydrogenation catalyst or a waste hydrocracking catalyst; Preferably, the mass concentration of the metal salt solution is 0.01wt%-3wt%; More preferably, the mass concentration of the metal salt solution is 0.5wt%-2.5wt%.

4. The preparation method according to claim 3, characterized in that: The first acid solution includes a nitric acid solution; Preferably, the mass concentration of nitric acid in the first acid solution is 3wt%-30wt%; More preferably, the mass concentration of nitric acid in the first acid solution is 5wt%-25wt%.

5. The preparation method according to claim 3, characterized in that: Before the impurity removal calcination, the first oxide is first ground to 100-500 mesh; Preferably, the temperature of the impurity removal calcination is 600°C-900°C; More preferably, the temperature of the impurity removal calcination is 600°C-800°C; Preferably, the impurity removal calcination time is 120-480 min.

6. The preparation method according to claim 1, characterized in that: The temperature of the ion exchange is 60-100°C; Preferably, the ion exchange temperature is 80-100°C; Preferably, the ion exchange time is 1-6h; Preferably, the solid-liquid ratio of the FAU molecular sieve to the metal salt solution is 1:0.5-10 g / mL, and more preferably, the solid-liquid ratio of the FAU molecular sieve to the metal salt solution is 1:0.5-7 g / mL.

7. The preparation method according to claim 1, characterized in that: The molar ratio of each component in the composite FAU molecular sieve is: Alumina:silicon dioxide = 1:0.5-10; Alumina: MOH = 1: 5-30; Alumina: water = 1: 10-80; Alumina: acid metal salt = 1: 0.5-20; Alumina: MO = 1: 0.2-5; The MO is an oxide of an active metal in the composite FAU molecular sieve, and the MOH is a hydroxide of an active metal in the composite FAU molecular sieve; The active metals include two or more active metals selected from Fe, K, Cu, Mn or Zn.

8. The preparation method according to claim 1, characterized in that: The preparation method of the FAU molecular sieve comprises: a) mixing the aluminum source gel system and the silicon source gel system to obtain a gel solution; b) mixing the gel solution with a first alkali source to obtain a gel slurry solution; c) subjecting the gel slurry solution to a first crystallization reaction and a second crystallization reaction to obtain a molecular sieve seed solution; d) mixing an aluminum-containing solution, a silicon-containing solution and the molecular sieve seed solution to obtain the FAU molecular sieve; Preferably, said d) includes da) or db), The step da) comprises: mixing the aluminum-containing solution and the silicon-containing solution to obtain a gel mother solution; Then, the gel mother solution is mixed with the molecular sieve seed solution, and a first aging reaction and a third crystallization reaction are performed to obtain the FAU molecular sieve; The step db) comprises: mixing and extruding the aluminum-containing solution, the silicon-containing solution, the molecular sieve seed solution and auxiliary materials to obtain a molecular sieve precursor; Then, the molecular sieve precursor is subjected to a second aging reaction and a fourth crystallization reaction in sequence to obtain the FAU molecular sieve; Preferably, the auxiliary material comprises one or more of a shaping agent, a pore-forming agent or a lubricant; Preferably, the auxiliary material accounts for 2-15 wt% of the mass of the molecular sieve precursor.

9. The preparation method according to claim 8, characterized in that: The preparation method comprises: First, the FAU molecular sieve is prepared by using a), b), c) and da); secondly, the FAU molecular sieve is mixed with the metal salt solution and ion exchange is performed to obtain a composite FAU molecular sieve; and then the composite FAU molecular sieve is mixed with the auxiliary material, and then dried and the first calcination is performed to obtain the metal-modified molecular sieve; or First, the FAU molecular sieve is prepared by using a), b), c) and db); secondly, the FAU molecular sieve is mixed with the metal salt solution and ion exchange is performed to obtain a composite FAU molecular sieve; and the composite FAU molecular sieve is then dried and calcined in sequence to obtain the metal-modified molecular sieve; Preferably, the mass ratio of the composite FAU molecular sieve to the forming agent, the pore-forming agent and the lubricant is: 5-95: 5-95: 0.05-5: 0.01-5; Preferably, the drying temperature is 80-150°C; Preferably, the drying time is 0.1-5h.

10. A metal-modified molecular sieve, characterized in that: The metal-modified molecular sieve adsorbent is a metal-modified molecular sieve prepared by the preparation method of a metal-modified molecular sieve according to any one of claims 1 to 9.

11. Use of the metal-modified molecular sieve prepared by the method for preparing the metal-modified molecular sieve according to any one of claims 1 to 9, or the metal-modified molecular sieve according to claim 10, in adsorbing oxygen-containing compounds in hydrocarbon compounds.